2009
DOI: 10.1159/000228583
|View full text |Cite
|
Sign up to set email alerts
|

Colonization of <i>Gardnerella vaginalis</i> in Semen of Infertile Men: Prevalence, Influence on Sperm Characteristics, Relationship with Leukocyte Concentration and Clinical Significance

Abstract: Aims: To determine the prevalence of Gardnerella vaginalis in semen from infertile men and their negative effects on semen quality. Results: Cultures were positive in 24/108 infertile men (22.2%) and negative in controls. Infected semen showed no significant difference compared with non-infected semen. On the other hand, infected and non-infected semen presented significant differences in vitality, rapid and total progressive motility, normal head and mid-piece defects (p < 0.01) and combined anomalies (p < 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 9 publications
0
6
1
2
Order By: Relevance
“…Manca et al found a positive correlation between the presence of G. vaginalis infections and leukocytes, while sperm concentration, motility and morphology were found to deteriorate in the presence of G. vaginalis [20] . Andrade-Rocha concluded that the presence of G. vaginalis is not associated with either abnormal sperm characteristics or inflammatory response in infected men [30] . However, in this study, we found a positive correlation between the proportion of G. vaginalis genera and semen quality (see Table 3 ), including sperm concentration, motility, Kruger's strict morphology, antisperm-antibody (IgA), Atypical and Leucocytes – findings which differ from previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Manca et al found a positive correlation between the presence of G. vaginalis infections and leukocytes, while sperm concentration, motility and morphology were found to deteriorate in the presence of G. vaginalis [20] . Andrade-Rocha concluded that the presence of G. vaginalis is not associated with either abnormal sperm characteristics or inflammatory response in infected men [30] . However, in this study, we found a positive correlation between the proportion of G. vaginalis genera and semen quality (see Table 3 ), including sperm concentration, motility, Kruger's strict morphology, antisperm-antibody (IgA), Atypical and Leucocytes – findings which differ from previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, most abundant genera present in Hou et al's study were also identified abundant in our data, such as Lactobacillus (19.9%), Prevotella (8.51%), Finegoldia (2.73%), Corynebacterium (2.04%), Staphylococcus (1.46%) and Veillonella (1.04%). In addition, some of our relative abundant bacteria had been identified in previous studies which used PCR-based or culture methods to detect bacteria in semen or the male genital tract, such as Lactobacillus [18] , [22] , [29] , Pseudomonas [22] , [29] , Gardnerella [18] , [20] , [30] , [31] , Prevotella [29] , [32] and Haemophilus [22] . It shows the comparability and reliability of our sequencing data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Selon certains auteurs, G. vaginalis n'aurait pas d'impact sur les paramè tres spermatiques [24]. Mais pour d'autres, au seuil de 10 3 UFC/mL, la pré sence de G. vaginalis serait corré lé e à la pré sence d'une leucospermie et la bacté rie serait associé e à une alté ration des principaux paramè tres spermatiques (concentration, mobilité et morphologie spermatiques) en comparaison avec des patients té moins [25].…”
Section: Gardnerella Vaginalisunclassified
“…En cas de spermoculture positive isolé e à G. vaginalis, un contrôle de la spermoculture est né cessaire. En thé orie, aucun traitement antibiotique ne se justifie devant une spermoculture positive isolé e à G. vaginalis, é tant donné l'absence d'impact avé ré de cette bacté rie sur les paramè tres spermatiques [24] mais la SFM conseille, par mesure de pré caution, de traiter au-delà d'un seuil de 5,10 3 UFC/mL [6]. Le seuil de 5,10 3 UFC/mL est aussi celui retenu pour C. albicans dans le cadre de l'AMP.…”
Section: Quand Traiter ?unclassified